The Inca Garcilaso for the Parisian worldliness: Jean Baudoin and his publication in France of the second part of the Comentarios Reales - Laske, Trilce (2018)
This article deals with the conditions in France of the introduction of the second part of the Comentarios Reales in the early 1650s. Translated by a Parisian man of letters, whose labor needs were partly subjected to the demands of a wordly public, the first French version shifted the work of the Inca Garcilaso to another historiographical regime, based on a process of social and cultural conversion of the original text. This process illustrates one of the possible ways of reappropriation by other European spaces of works produced within the Hispanic imperial framework related to their American territories